Effects of Heat Treatment Systems on the Physical Properties of Coated Scots pine (Pinus sylvestris L.) and poplar (Populus euramericana) - Can, Ahmet; Can, Ahmet (North Carolina State Univ Dept Wood & Paper Sci, 2020)
Heat treatment is an environmentally friendly and efficient way to improve the properties of wood species. These treatments alter the substrates and can influence the surface properties of the varnish coatings. This paper investigated the effects of heat treatment on the physical properties of open and close systems Scots pine (Pinus sylvestris L.) and poplar (Populus euramericana) wood, coated with water-based, polyurethane based, and oil/wax-based varnishes. Heat treatment was applied at the temperatures of 190, 212 degrees C for pine and 180, 200 degrees C for poplar, respectively. Color, gloss, and roughness tests were carried out for each of the coatings. Higher mass loss occurred in pine samples with heat treatment as compared to vacuum-heat treatment. Gloss decreased in OIL+WAX treatment and color change increased after the heat treatment, but these results were inhibited with vacuum-heat treatment. Maximum roughness was obtained in PUR varnishes and minimum roughness in OIL + WAX samples. The low roughness values provide some advantages in application.
Keywords: Aqua Varnish; Pur Varnish; Oil Plus Wax Varnish; Close System Heat Treatment; Surface Properties